TO THE IDEA OF GLOBAL CIVIL SOCIETY - E.N. SADOVAIA (Advanced Engineering Research, 2007)
The role of civil society is changing nowadays under the pressure of global problems, spread of national borders and constantly growing process of informatisation. It is not only linked to the state but overcomes the state frontiers to solve up-to-date problems of mankind. Thus civil society becomes global that can be recognized not in quantity of its members but in the level of development of its cosmopolitan, global thinking.